Dental Neglect Score amongst Orthodontic Braces patients in Punjab Dental Hospital - Shibra Khurshid, Muttayaba Irfan, Aamina Sagheer, Hafiza Asma Jawaid, Asmi Shaheen, Maham Munir (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Dental Neglect refers to ones attitudes and behavior that cause harmful consequences in oral health. Subjects with greater dental negligence are linked with more caries, lesser remaining teeth, irregular visits to the dentist and are more likely to have prolonged time duration between their dental appointments.. The Dental Neglect Scale (DNS) is valued as a reliable measure of dental negligence in various samples of children, adolescents and adults. Maintenance of conscientious practice related to oral health is key to success in orthodontic patients. This is because orthodontic appliances facilitate the accumulation of plaque by making cleaning difficult over the teeth. Failure to keep up the proper oral hygiene measures can lead to accumulation of plaque. This causes gingival inflammation and damages periodontal health. Aim: To determine dental negligence score among orthodontic patients with braces and assess their associated oral hygiene practices. Study Design: Cross sectional study Place and duration of the study: This study took 6 months to complete and was conducted in Punjab Dental Hospital, Lahore, Pakistan. Methodology :104 orthodontic patients willing to participate and who had given informed consent were chosen for the study. Questionnaires were distributed and data was analyzed using SPSS 2020. Results: Before starting orthodontic treatment only 14% of respondents went regularly to the dentist and majority 64% had never been to a dentist before. However, after starting the orthodontic treatment 88% of the respondents became regular in their visits. This shows their dental negligence before and after starting the orthodontic treatment. Percentage of respondents brushing twice daily are around 70 %, using soft tooth brush are 77%, combining horizontal and vertical technique of brushing are 64%. Interdental brush is used by 66% of the respondents. However, other oral hygiene and dental care measures are inadequately maintained by orthodontic patients at home. This is especially true with regards to use of floss which is done by only 4% of the respondents. Conclusions: Dental neglect results in numerous harmful effects to the oral health. This study has shown variation in oral hygiene practices among responding patients. Orthodontist should encourage different practices that enhance oral hygiene in patients. Patients should also understand the increased need to maintain oral hygiene with use of braces and hence apply all the preached dental care and oral hygiene measures. Keywords: Dental negligence scale, orthodontic patients with fixed appliances, braces, oral hygiene